2016
DOI: 10.21833/ijaas.2016.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effects of edible brown seaweeds in rats

Abstract: The present study is focused to evaluate the effect of three different brown seaweeds on blood pressure and heart rate (HR) using spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto (WKY) rats. The seaweeds, Turbinaria ornata (T. ornata), Sargassum species (Sargassum sp.) and Padina tetrastromatica (P. tetrastromatica), were extracted in cold water and freeze-dried. Anaesthetised rats were prepared for direct blood pressure measurements with the changes in HR also being monitored. Rats were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, this effect was not observed with other brown algae tested. Evaluation of the ionic constitution present in the extracts disclosed that the salt solution with an equivalent ionic substance of each seaweed extract does not lead to a significant decrease in blood pressure in Sprague-Dawley rats [60]. The antiproliferative activities of T. ornata have been included in Table 2.…”
Section: Antidiabetic Activitiesmentioning
confidence: 99%
“…However, this effect was not observed with other brown algae tested. Evaluation of the ionic constitution present in the extracts disclosed that the salt solution with an equivalent ionic substance of each seaweed extract does not lead to a significant decrease in blood pressure in Sprague-Dawley rats [60]. The antiproliferative activities of T. ornata have been included in Table 2.…”
Section: Antidiabetic Activitiesmentioning
confidence: 99%
“…In this context, marine seaweeds have vast biodiversity because they are exposed to a wide range of environmental factors that differ from those of terrestrial plants, leading to the pro-duction of secondary metabolites with various characteristics and applicability. Various in vitro, in vivo, and clinical studies have reported on the efficacy of seaweeds and their natural products for reducing the risk of CVD [ 17 , 18 ]. For example, several studies have revealed an association between dietary intake of seaweed and increased life expectancy or reduced incidence of certain diseases, such as CVD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among many other possible examples, the use of seaweed and some of its components as bio-resources for fuel production [ 15 , 16 ], the use of seaweed cellulose to produce new cellulose derivative fibbers [ 17 ], and the use of seaweed-derived polysaccharide-based composites for food packaging and pharmaceutical applications including tissue engineering, drug delivery, and wound dressing [ 18 ] can be emphasized. In fact, the biodiversity within red (Rhodophyta), green (Chlorophyta) and brown (Phaeophyta) macroalgae offers the possibility of finding a wide variety of compounds, like carbohydrates, protein and minerals, as well as a rich source of health-promoting secondary metabolites with interesting properties and applications [ 13 , 19 , 20 , 21 ], including prevention and treatment of cardiovascular diseases risk factors [ 22 , 23 , 24 , 25 ]. Most macroalgae products described in the scientific literature as having antihypertensive and/or anti-obesity effects are the whole extract (aqueous or alcoholic), or fractions rich in a particular type of compound (e.g., fucoidans, alginates, phlorotannins) [ 22 , 23 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies on the efficacy of these products are quite advanced, including animal studies, human studies and some in-clinical studies. Although they are interesting works, they are not the subject of this review, so we draw our readers’ attention to excellent reviews on this subject [ 22 , 23 , 24 , 25 , 27 , 28 ]. These extracts/fractions’ chemical composition is not unequivocally known.…”
Section: Introductionmentioning
confidence: 99%